Effects of Urtica dioica L. seed on lipid peroxidation, antioxidants and liver pathology in aflatoxin-induced tissue injury in rats - Yener, Zabit; Celik, Ismail; Ilhan, Fatma; Bal, Ramazan (Pergamon-Elsevier Science Ltd, 2009)
This study was carried out to investigate the hepatoprotective and antioxidant properties of Urtica dioica L seeds (LIDS) extract against aflatoxin (AF)-exposure in rats. The preventive potential and antioxidant capacity of the plant's extract was evaluated by liver histopathological changes, measuring serum marker enzymes, antioxidant defense systems and lipid peroxidation (Malondialdehyde, MDA) content in some tissues of rats. Eighteen rats were randomly divided into one of three experimental groups: control, AF-treated group and AF+UDS-treated group. Rats in control group were fed with a diet without AF. Rats in AF-treated group and AF+UDS-treated group received approximately 25 mu gr of AF/rat/day. AF+UDS groups also received 2 mL of LIDS oils/rat/day by gavage for 90 days. Administration of LIDS extract restored the AF-induced imbalance between MDA and antioxidant system towards near normal particularly in liver. Hepatoprotection by LIDS is further substantiated by the almost normal histologic findings in AF+UDS-treated group as against degenerative changes in the AF-treated rats. It is concluded that LIDS has a hepatoprotective effect in rats with aflatoxicosis, probably acting by promoting the antioxidative defense systems. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Aflatoxicosis; Urtica dioica L seed; Histopathology; Biochemistry; Rat